VGI ed emergenze - Lupia, Flavio; Minghini, Marco; Napolitano, Maurizio; Palmas, Alessandro; Sarretta, Alessandro (GEOmedia, 2016)
Availability of up-to-date geographic datasets, including the information voluntarily created by ordinary people, is crucial for disaster management in areas affected by catastrophic events and humanitarian crises. OpenStreetMap (OSM) is the most popular Volunteered Geographic Information (VGI) project that has been extensively used for collaborative mapping in areas affected by natural disasters. This article provides an overview on how OSM data are exploited in disaster response scenarios and illustrates their specific application during the recent Italian earthquakes.